The Public Relations–Social Responsibility binomial in post-pandemic sustainable and regenerative tourism: An innovative post-pandemic tourism approach to the 2030 Agenda for Sustainable Development, with Barcelona as a benchmark - Huerta Molinero, Ana María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Regenerative tourism implies the joint evolution of the human being with nature through the investigation of predispositions, procedures and experiences. Regeneration is based on going beyond sustainability, a vital circumstance for the efficient fulfillment of the 17 SDGs of the 2030 Agenda for Sustainable Development. The methodology used is sequential, where after a literature review, different case studies have been analyzed using secondary sources to verify the presence of the PR-SR binomial. Barcelona can be a reference for getting out of the post-pandemic crisis, so that it can also be applied to the rest of Spain and worldwide.